Effects of powdery mildew (Blumeria graminis) severity on durum wheat cultivars - Tomás A.; Solís I. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Powdery mildew, caused by Blumeria graminis, is an important disease of durum wheat (Triticum turgidum L. var. durum) in Mediterranean conditions. In 1999, the environmental conditions were very favourable for the development of the disease in the South of Spain and the mycelium of the pathogen was evident from February to May in almost all the durum wheat cultivars sown by Agrovegetal S.A. in Jerez de la Frontera (Cádiz) and Escacena del Campo (Huelva). The cultivars showed a large variation in disease severity in the field, ranging from 0 to 70 per cent, with different values in each repetition of the same place due to the spatial irregularity of the inoculum. The yield data collected in each plot of the same cultivar in Escacena del Campo is highly correlated with his final disease severity. In Jerez de la Frontera the yield ranking of varieties is also correlated with their powdery mildew severity.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)